(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, we will discuss in detail Jane Austen’s work "Pride and Prejudice" and a comparative analysis of the characters in the work. Nowadays, "Andisha and Pride" is constantly at the top of the list of "most favorite books" among literary scholars and readers. It has sold more than 20 million copies, becoming one of the most popular novels in English literature and has inspired many writers in modern literature.